2013
DOI: 10.1155/2013/269583
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Use on the Dorsal Hands at the Beach

Abstract: Background. Since skin of the dorsal hands is a known site for the development of cutaneous squamous cell carcinoma, an epidemiologic investigation was needed to determine if beachgoers apply sunscreen to the dorsal aspect of their hands as frequently as they apply it to other skin sites. Aim. The aim of the current study was to compare the use of sunscreen on the dorsal hands to other areas of the body during subtropical late spring and summer sunlight exposure at the beach. Materials and Methods. A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…1 Although many factors such as advanced age, low Fitzpatrick skin types, and male gender have been associated with an increased risk of developing skin cancer, unprotected UVR exposure has been reported as the single most important environmental risk factor. 2 Many epidemiological studies in the literature suggest that UVR from sun exposure and sunburns at early ages are associated with skin cancers in adulthood. 3e5 It was reported that a history of sunburn in early life almost doubles the risk of developing melanoma in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although many factors such as advanced age, low Fitzpatrick skin types, and male gender have been associated with an increased risk of developing skin cancer, unprotected UVR exposure has been reported as the single most important environmental risk factor. 2 Many epidemiological studies in the literature suggest that UVR from sun exposure and sunburns at early ages are associated with skin cancers in adulthood. 3e5 It was reported that a history of sunburn in early life almost doubles the risk of developing melanoma in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of demographic and behavioral factors relating to sunscreen application have identified groups most at risk for sun‐related damage. Several studies have shown that women are more likely to use sunscreen than men and that men are less likely to apply sunscreen to all sunlight‐exposed areas . In addition, older individuals (>60 years) are more likely to apply sunscreen .…”
Section: Reported Mean Application Amount Of Lotion Sunscreensmentioning
confidence: 99%
“…Individuals who have outdoor lifestyles, live in sunny climates, and have fair phototypes will experience the greatest degree of photoaging . Face, neck, legs, and the dorsal hands get the most sunlight exposure and are hence exposed to an increased risk of photodamage such as skin cancer and photoaging .…”
mentioning
confidence: 99%
“…Nonmelanoma skin cancers are the most common types of cancer in the white population and represent a serious health burden in sun‐exposed populations . Regular sunscreen use, together with avoiding sun exposure during the sun's zenith and wearing clothes, is one of the most important actions to prevent skin cancer and other photodamages .…”
mentioning
confidence: 99%
See 1 more Smart Citation